2008
DOI: 10.1212/01.wnl.0000324919.86696.a9
|View full text |Cite
|
Sign up to set email alerts
|

Antiepileptic drug use and rates of hip bone loss in older men

Abstract: Objective: To test the hypotheses that older community dwelling men taking non-enzymeinducing antiepileptic drugs (NEIAEDs) and those taking enzyme-inducing antiepileptic drugs (EIAEDs) have increased rates of hip bone loss. Methods:We ascertained antiepileptic drug (AED) use (interviewer-administered questionnaire with verification of use by containers) and measured hip bone mineral density (BMD) (using dual energy x-ray absorptiometry) at baseline and an average of 4.6 years later in a cohort of 4,222 older … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0
9

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(69 citation statements)
references
References 36 publications
3
57
0
9
Order By: Relevance
“…Another noteworthy study in this arena was a large, community-based study of elderly men in whom bone density was measured twice, an average of 4.6 years apart (17). After adjustment for a large number of potential confounders, those taking inducing AEDs had a rate of bone loss no different from controls, whereas those taking non-inducing AEDs had an accelerated rate of bone loss; in fact, this was larger in patients who were being treated at both time points than in patients who were being treated only at one time point, consistent with a dose-response relationship.…”
Section: Bone and Vitamin D Metabolismmentioning
confidence: 99%
“…Another noteworthy study in this arena was a large, community-based study of elderly men in whom bone density was measured twice, an average of 4.6 years apart (17). After adjustment for a large number of potential confounders, those taking inducing AEDs had a rate of bone loss no different from controls, whereas those taking non-inducing AEDs had an accelerated rate of bone loss; in fact, this was larger in patients who were being treated at both time points than in patients who were being treated only at one time point, consistent with a dose-response relationship.…”
Section: Bone and Vitamin D Metabolismmentioning
confidence: 99%
“…15) The prospective study showed a significant bone loss in the femoral neck of elderly male patients administered gabapentin. 16) However, the mechanism of the effect of gabapentin on bone metabolism is uncertain and limited data are available with regard to the effects of the new AEDs on bone metabolism. Thus, in the present study, we investigated the effects of phenytoin, gabapentin, and levetiracetam on bone strength, bone mass, and bone turnover in rats.…”
mentioning
confidence: 99%
“…Long-term treatment with AEDs is associated with a facilitated rate of bone loss, and consequently an increased risk of bone fractures (10,19,41). Although topiramate and lamotrigine were approved for clinical use, there are limited data regarding their effects on bone metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term treatment with antiepileptic drugs (AEDs) has been correlated with bone loss and consequently increased risk of bone fractures (10,19,41). Bone is maintained by continuous remodeling, involving bone formation and bone resorption (31).…”
mentioning
confidence: 99%